2018
DOI: 10.1111/cbdd.13398
|View full text |Cite
|
Sign up to set email alerts
|

Insight into selective mechanism of class of I‐BRD9 inhibitors toward BRD9 based on molecular dynamics simulations

Abstract: Recently, bromodomain-containing protein 9 (BRD9), 7 (BRD7), and 4 (BRD4) have been potential targets of anticancer drug design. Molecular dynamic simulations followed by molecular mechanics Poisson-Boltzmann surface area calculation were performed to study the selective mechanism of I-BRD9 inhibitor H1B and its derivatives N1D, TVU, and 5V2 toward BRD9 and BRD4. The rank of our calculated binding free energies agrees with that of the experimental data. The results show that binding free energy of H1B to BRD7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…For example, small-molecule inhibitors of the BRD9 bromodomain selectively suppress tumor cell proliferation and survival and induce apoptosis. 27,75,102,103 Indeed, scientists have researched and developed several effective BRD9 bromodomain inhibitors, such as BRD9 selective inhibitors (I-BRD9, 104 BI-7273, 105 and BI-9564 106 ) and BRD7/9 inhibitors. 107,108 LP99 is the first reported selective BRD7/9 inhibitor that effectively inhibits the binding of BRD7/9 to acetylated histones in vivo and in vitro; Moreover, LP99 inhibits the secretion of proinflammatory cytokine IL-6.…”
Section: Cancer Therapeutics For Targeting Brd9mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, small-molecule inhibitors of the BRD9 bromodomain selectively suppress tumor cell proliferation and survival and induce apoptosis. 27,75,102,103 Indeed, scientists have researched and developed several effective BRD9 bromodomain inhibitors, such as BRD9 selective inhibitors (I-BRD9, 104 BI-7273, 105 and BI-9564 106 ) and BRD7/9 inhibitors. 107,108 LP99 is the first reported selective BRD7/9 inhibitor that effectively inhibits the binding of BRD7/9 to acetylated histones in vivo and in vitro; Moreover, LP99 inhibits the secretion of proinflammatory cytokine IL-6.…”
Section: Cancer Therapeutics For Targeting Brd9mentioning
confidence: 99%
“…117 Studies on the selection mechanism of I-BRD9 for the BRD9 bromodomain have demonstrated that several residues in the ZA and ZB loops of the bromodomain, such as Asp144, Ile53, Lys91, Thr104, Pro82, Asn140, Asn100, and Phe44, can be used as important references for designing BRD9 inhibitors. 104 The imidazo [1,5-a] pyrazin-8 (7H) -one derivative was designed and synthesized using the interaction of the inhibitor with the Asn and Tyr residues to inhibit BRD9 activity. 118 In addition to the synthesis and design of protein inhibitors, targeting protein degradation by hijacking the ubiquitinproteasome system can be another therapeutic strategy.…”
mentioning
confidence: 99%
“…Finally, we did not explore the mechanism of BRD-containing protein genes in HCC and evaluate the potential therapeutic effects between BRDs and anticancer drugs. Recent studies have focused on the selective mechanism of inhibitors toward BRD-containing protein genes such as BRD4 and BRD9 based on molecular dynamics simulations [ 56 , 57 ]. Further researches are needed to explore the exact mechanism and therapeutic roles of BRDs in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of the BRD9 subunit of the BAF and ncBAF complexes leads to cell death in both SS and MRT (122, 123). This is particularly interesting given the recent development of potent and specific BRD9 targeting compounds (124128). Another synthetic lethal target for SS is the DNA damage response kinase ATR, which has been shown to impair growth of patient-derived SS xenografts (129).…”
Section: Novel Epigenetic Therapeutic Approachesmentioning
confidence: 99%